2011
DOI: 10.1093/hmg/ddr512
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the human MTM1 p.R69C mutation in murine Mtm1 results in exon 4 skipping and a less severe myotubular myopathy phenotype

Abstract: X-linked myotubular myopathy (MTM) is a severe neuromuscular disease of infancy caused by mutations of MTM1, which encodes the phosphoinositide lipid phosphatase, myotubularin. The Mtm1 knockout (KO) mouse has a severe phenotype and its short lifespan (8 weeks) makes it a challenge to use as a model in the testing of certain preclinical therapeutics. Many MTM patients succumb early in life, but some have a more favorable prognosis. We used human genotype-phenotype correlation data to develop a myotubularin-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 38 publications
5
61
0
Order By: Relevance
“…We next sought to measure PI3P levels in our dKO animals, first by using an ELISA technique previously described for Mtm1 KOs (10). Using this ELISA on muscle extracts from P35 mice ( Figure 3A), we again found that PI3P levels were significantly increased in Mtm1 KOs.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…We next sought to measure PI3P levels in our dKO animals, first by using an ELISA technique previously described for Mtm1 KOs (10). Using this ELISA on muscle extracts from P35 mice ( Figure 3A), we again found that PI3P levels were significantly increased in Mtm1 KOs.…”
Section: Resultsmentioning
confidence: 91%
“…Approximately one-third of affected boys die in the first year of life, and survivors manifest significant morbidities, including chronic ventilator and wheelchair dependence, and drastically reduced lifespan (8). MTM1 functions to dephosphorylate phosphatidylinositol-3-phosphate (PI3P) and phosphatidylinositol-3,5-bisphosphate [PI (3,5)P2], and we have documented in vertebrate models that loss of MTM1 results in significantly increased PI3P levels (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous ex vivo investigations of this model revealed different histopathological features including myofiber hypotrophy and structural abnormalities of the neuromuscular junction. 17,20,21 Using intravital imaging, we were indeed able to detect an increased proportion of atrophic fibers, and an abnormal shape of the neuromuscular junctions in the Mtm1 knockout mice. Our in vivo observations support the notion that the muscle weakness correlates with hypotrophy, and that functional defects of the neuromuscular transmission represent one of the disease causes.…”
Section: Intravital Monitoring Of a Muscle Diseasementioning
confidence: 86%
“…8 Different potential causes of the muscle weakness have been proposed for XLMTM, as triad structural defects, [9][10][11] unbalanced autophagy and protein homeostasis, [12][13][14] satellite cells alterations 15 or anomalies of the neuromuscular junction. 16,17 However, monitoring cellular pathological hallmarks in living mammalian models of XLMTM was not achieved to date, and the knowledge of the cellular pathology of XLMTM mainly relies on in vitro or ex vivo observations in mammalian models, 9,13,[18][19][20][21] or on data from more evolutionary-distant models as zebrafish, 10,17 drosophila, 22 C. elegans 23 or yeast. 18,24,25 Monitoring the structure of muscles in place is thus of importance to follow disease progression and potential amelioration upon treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle function has also been extensively studied in a mouse model knocked in for MTM1 p.R69C (c.205C > T) [129], a mutation associated with a less severe form of myotubular myopathy [130,131]. The MTM1 p.R69C mutation putatively affects the binding domain of PI(3)P/PI(3,5)P 2 but not its catalytic domain and should therefore result in a phosphatase binding less substrate leading to a hypofunctional enzyme.…”
Section: Mtm1 Bin1 and Dnm2 Related Disordersmentioning
confidence: 99%